Lymphangiogenesis in Oral Squamous Cell Carcinoma: Correlation with VEGF-C Expression and Lymph Node Metastasis - Manar A. Abdul-Aziz; Amina K. Amin; Dalia H. El-Rouby; Olfat G. Shaker (International Journal of Dentistry)
Background. Oral squamous cell carcinoma (OSCC) is the most common oral malignancy that preferentially spreads to the cervical lymph node which, when involved, complicates the anticancer therapy and threatens the patient life. It was suggested that lymph node metastasis may be facilitated by lymphangiogenesis. VEGF-C is one of the most important lymphangiogenic inducers that promotes the lymphatic vessels growth and supports the survival of adult lymphatic endothelial cells. Methods. Lymphatic vessels density (LVD) and LV morphometry were digitally evaluated using D2-40. The expression of VEGF-C was also assessed using immunohistochemistry and real-time polymerase chain reaction in 6 normal oral mucosa cases and 72 cases of OSCC. The correlation between LVD and LV morphometry, VEGF-C, and lymph node metastasis was statistically assessed. Results. A positive cytoplasmic expression of VEGF-C was detected in both epithelial and connective tissue cells in 97% of OSCC, while all normal tissues reacted negatively. A greater expression of VEGF-C was associated with larger and more dilated LV and lymph node metastasis but not with LVD. Conclusion. VEGF-C is actively involved in the invasion and metastasis of OSCC via inducing morphological changes in LV. VEGF-C may be a promising target for anticancer therapy.